Genome and transcriptome based comparative analysis of Tilletia indica to decipher the causal genes for pathogenicity of Karnal bunt in wheat - Kalpana Singh; Pradeep Sharma; Sarika Jaiswal; Pallavi Mishra; Ranjeet Maurya; Senthilkumar K Muthusamy; MS Saharan; Rahul Singh Jasrotia; Jitender Kumar; Shefali Mishra; Sonia Sheoran; GP Singh; et al. (BMC Plant Biology, 2024)
Abstract Tilletia indica Mitra causes Karnal bunt (KB) in wheat by pathogenic dikaryophase. The present study is the first to provide the draft genomes of the dikaryon (PSWKBGD-3) and its two monosporidial lines (PSWKBGH-1 and 2) using Illumina and PacBio reads, their annotation and the comparative analyses among the three genomes by extracting polymorphic SSR markers. The trancriptome from infected wheat grains of the susceptible wheat cultivar WL711 at 24 h, 48h, and 7d after inoculation of PSWKBGH-1, 2 and PSWKBGD-3 were also isolated. Further, two transcriptome analyses were performed utilizing T. indica transcriptome to extract dikaryon genes responsible for pathogenesis, and wheat transcriptome to extract wheat genes affected by dikaryon involved in plant-pathogen interaction during progression of KB in wheat. A total of 54, 529, and 87 genes at 24hai, 48hai, and 7dai, respectively were upregulated in dikaryon stage while 21, 35, and 134 genes of T. indica at 24hai, 48hai, and 7dai, respectively, were activated only in dikaryon stage. While, a total of 23, 17, and 52 wheat genes at 24hai, 48hai, and 7dai, respectively were upregulated due to the presence of dikaryon stage only. The results obtained during this study have been compiled in a web resource called TiGeR ( http://backlin.cabgrid.res.in/tiger/ ), which is the first genomic resource for T. indica cataloguing genes, genomic and polymorphic SSRs of the three T. indica lines, wheat and T. indica DEGs as well as wheat genes affected by T. indica dikaryon along with the pathogenecity related proteins of T. indica dikaryon during incidence of KB at different time points. The present study would be helpful to understand the role of dikaryon in plant-pathogen interaction during progression of KB, which would be helpful to manage KB in wheat, and to develop KB-resistant wheat varieties.